2013
DOI: 10.1017/s1368980013001389
|View full text |Cite
|
Sign up to set email alerts
|

Associations between access to farmers’ markets and supermarkets, shopping patterns, fruit and vegetable consumption and health indicators among women of reproductive age in eastern North Carolina, USA

Abstract: Objective We examined associations between access to food venues (farmers’ markets and supermarkets), shopping patterns, fruit and vegetable consumption and health indicators among women of reproductive age in eastern North Carolina, USA. Design Access to food venues was measured using a Geographic Information System incorporating distance, seasonality and business hours, to quantify access to farmers’ markets. Produce consumption was assessed by self-report of eating five or more fruits and vegetables daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…This finding is supported by other studies of other low-income, minority populations that show frequent use of super-stores (eg, Wal-Mart) for produce purchases in urban areas; these areas have limited access to supermarkets or alternative healthful food options, such as farmers' markets and community gardens. 46,47 A recently published study of low-income African American and Latina women in Forsyth County, North Carolina reported that price, convenience, and a lack of acceptance of SNAP or WIC benefits influenced shoppers choosing a super-store vs a farmers' market. 45 In our study, most women did not believe FMs were more expensive or less convenient than groceries or supermarkets, regardless of whether or not they were FM users.…”
Section: Farmers' Market Utilization -Nuss Et Almentioning
confidence: 99%
“…This finding is supported by other studies of other low-income, minority populations that show frequent use of super-stores (eg, Wal-Mart) for produce purchases in urban areas; these areas have limited access to supermarkets or alternative healthful food options, such as farmers' markets and community gardens. 46,47 A recently published study of low-income African American and Latina women in Forsyth County, North Carolina reported that price, convenience, and a lack of acceptance of SNAP or WIC benefits influenced shoppers choosing a super-store vs a farmers' market. 45 In our study, most women did not believe FMs were more expensive or less convenient than groceries or supermarkets, regardless of whether or not they were FM users.…”
Section: Farmers' Market Utilization -Nuss Et Almentioning
confidence: 99%
“…Others may be older or unemployed and have no children, and have a smaller activity space, mainly staying in close proximity to the residential address. Still other women may be rural dwellers and have a longer distance to drive to shop for food compared to more urban women (Hillier et al, 2011; Jilcott Pitts et al, 2013). It is important to study travel patterns of a variety of demographic groups (e.g., employment status, urban or rural residence) in order to inform future interventions to promote health among various groups.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of use in the current study is similar to other studies of FTC outlet use among WIC program participants. 28,3638 In a study on usage patterns of a newly established farmers’ market located adjacent to a clinic in Miami, Florida, Grin et al 37 found that only 35% of lower income women receiving services at the clinic reported visiting the market in the past year. Jilcott-Pitts et al 36 observed that about 25% of lower income women in North Carolina used local farmers’ markets.…”
Section: Discussionmentioning
confidence: 99%